Social Consequences of Witchcraft Accusations: Marriage, Divorce, and Community Exclusion in Zanzibar - Faki, Bakari Khatib; Ahmed, Issa G. (PT. Riset Press International, 2025)
This study examines the social consequences of witchcraft accusations in Zanzibar with reference to how such accusations affected marriage, family (Divorce) and community cohesion. The study intends to learn the functioning of beliefs in witchcraft as a mechanism of stigma and social control and symbolic domination in the current Islamic and Swahili cultural systems. Depending on the analysis of secondary data and using only the qualitative exploratory design, the study relied on academic sources, ethnographies, nongovernmental organizations report, and policy documents on witchcraft beliefs and family dynamics in Africa. The analysis of data was performed thematically with references to the theory of stigma by Goffman and Bourdieu, notions of habitus and symbolic power. Findings show that witchcraft accusations divide marriages, promotes divorce, leads to gender inequality, intergenerational exclusion, and poverty. They also erode the social welfare systems on the basis of kinship and reciprocity, as well as undermine communal trust. The paper has made contributions to the sociological and policy discussions by the conceptualization of witchcraft as a form of socially organized phenomenon and offers policy-based interventions that are culturally grounded to enhance the inclusion, gender equity, and resilience of the communities in Zanzibar.